2013
DOI: 10.1007/s10753-013-9691-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Insulin to Decrease Septic Shock-Induced Myocardial Depression in a Porcine Model

Abstract: Insulin is known to attenuate septic shock-induced myocardial depression. Possible mechanisms include an anti-inflammatory or inotropic effect of insulin. The objective of this study was to determine whether the mechanism of action of insulin in attenuating septic shock-induced myocardial depression is through an immunomodulatory effect. Fourteen pigs were assigned to one of two groups. Both groups received a 4-h infusion of lipopolysaccharide endotoxin from Escherichia coli 0111:B4. Group 2 additionally recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This might explain why Levenbrown et al (2013) observed a delayed TNF-␣ peak concentration only at 2.5 h p.a. of LPS, as the i.v.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 97%
See 1 more Smart Citation
“…This might explain why Levenbrown et al (2013) observed a delayed TNF-␣ peak concentration only at 2.5 h p.a. of LPS, as the i.v.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 97%
“…With the exception of Warren et al (1997) and Levenbrown et al (2013), who surprisingly determined a maximal plasma concentration of TNF-␣ only at 1.5 and 2.5 h post administration (p.a.) of LPS, respectively, the peak concentration of TNF-␣ is unarguably established at 1 h p.a.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Intramuscular anesthesia (choice of medications and dosing) was based on a protocol used in our laboratory for prior studies. Intravenous anesthetic medications and dosing were based on published recommendations [7,8]. The pigs were then given a 30-min stabilization period.…”
Section: Anesthesia and Monitoringmentioning
confidence: 99%
“…Experimental studies have been performed to support the use of GIK in septic shock, although the primary mechanism through insulin improves cardiac performance in septic shock is inconsistent among studies (36,37). Several clinical studies have addressed the use of GIK in patients with septic myocardial depression (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%